The Effect of Local Fiscal Variables on Local Economic Growth in Türkiye - Cihan Yüksel; Mehmet Songur (Transylvanian Review of Administrative Sciences, 2025)
The effects of fiscal decentralization, which is a proportional value, on national economic growth and the effects of local expenditures and revenues, which are absolute values, on local economic growth are distinct areas of study. In this study, the effects of local fiscal variables of 81 provinces in Türkiye on local economic growth were tested using the panel data technique for the period 2008–2022. The findings of the study indicate that local tax revenues, transfer revenues (grants) from the central government, population, and the schooling rate have a significant and positive impact on local GDP. The positive impact of local tax revenues is relatively low, with a value close to zero. While the impact of grants is greater than that of tax revenues, it can be said that population and schooling rates have considerable effects. No significant impact of local public expenditures and other local revenues on local GDP was found. The findings indicate that local fiscal variables in Türkiye should undergo structural transformations to eliminate their inadequacy in increasing local economic capacity.